A river lost : the life and death of the Columbia - Harden, Blaine (New York : W.W. Norton, 1996)
Details the destruction of the Columbia River in the Pacific Northwest by well-intentioned Americans who saw only the benefits of the dam-building, power plant and irrigation projects, not realizing the longterm effects of killing the river.
Includes bibliographical references and index.
Library Journal.
Publisher's Weekly.
Wilson's Public Library.
Adult
Keywords: Economic development -- Environmental aspects -- Columbia River Region; Economic development -- Social aspects -- Columbia River Region; Environmental degradation -- Columbia River Region; Water resources development -- Columbia River Region -- History; Economic development -- Environmental aspects; Economic development -- Social aspects; Water resources development -- History; Columbia River Region -- Environmental aspects